IMPLEMENTASI TEORI SUPER PADA PROGRAM LAYANAN BIMBINGAN DAN KONSELING KARIR UNTUK MAHASISWA PERGURUAN TINGGI - Anaway Irianti Mansyur; Dini Chairunnisa; Dede Rahmat Hidayat (Universitas Negeri Medan, 2019)
This literature study of guidance and counseling service programs in high school careers aim to be able to plan careers in the future. Many challenges will be faced by students in determining careers, including career uncertainty, access to information and career development programs, and economic and technological challenges. To anticipate the challenges of the hands it is necessary for universities to provide optimal service to the development of student careers. The existence of a super theory career guidance program that focuses on developing vocational identity (vocational identity) in early adulthood, is expected to help early adults in developing vocational identities as a whole, so that adolescents avoid the confusion of role confusion, especially the role of vocational identity.Keywords: Theory Super, Guidance And Counseling, Career